Decision making support tool: ahp to purchase a business management software - Bernini, Ana Caroline de Oliveira; Gomes, Thiara Cezana; Servare Junior, Marcos Wagner Jesus (Brazilian Journal of Production Engineering, 2022)
This paper was prepared with the aim of showing how decision-making can be solved with specific foundation and data. This work will present a multicriteria decision-making process for choosing a business management software for processes related to foreign trade in a medium-sized company, with the help of the AHP (Analytic Hierarchy Process) methodology, using objective, criteria and alternatives. As an initial step for the development of this work, bibliographical research was carried out, in which key articles associated with the theme were selected: “methods to support decision making”. For the object of data collection, interviews were conducted with the company Riomar Trading LTDA, using the SuperDecisions software, which used mathematical tools through pairwise comparisons of criteria and alternatives, thus obtaining the result for ideal decision making when purchasing a business management software. The study determines that the use of the AHP methodology in decision making provides information that adds value at the time of a complex and precise choice.